Re‐evaluating fetal scalp pH thresholds: An examination of fetal pH variations during labor - Aude Girault; Camille Le Ray; Charles Garabedian; François Goffinet; Xavier Tannier (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Since the 1970s, fetal scalp blood sampling (FSBS) has been used as a second‐line test of the acid–base status of the fetus to evaluate fetal well‐being during labor. The commonly employed thresholds that delineate normal pH (>7.25), subnormal (7.20–7.25), and pathological pH (<7.20) guide clinical decisions. However, these experienced‐based thresholds, based on observations and common sense, have yet to be confirmed. The aim of the study was to investigate if pH drop rate accelerates at the common thresholds (7.25 and 7.20) and to explore the possibility of identifying more accurate thresholds. Material and methods A retrospective study was conducted at a tertiary maternity hospital between June 2017 and July 2021. Patients with at least one FSBS during labor for category II fetal heart rate and delivery of a singleton cephalic infant were included. The rate of change in pH value between consecutive samples for each patient was calculated and plotted as a function of pH value. Linear regression models were used to model the evolution of the pH drop rate estimating slope and standard errors across predefined pH intervals. Exploration of alternative pH action thresholds was conducted. To explore the independence of the association between pH value and pH drop rate, multiple linear regression adjusted on age, body mass index, parity, oxytocin stimulation and suspected small for gestational age was performed. Results We included 2047 patients with at least one FSBS (total FSBS 3467); with 2047 umbilical cord blood pH, and a total of 5514 pH samples. Median pH values were 7.29 1 h before delivery, 7.26 30 min before delivery. The pH drop was slow between 7.40 and 7.30, then became more pronounced, with median rates of 0.0005 units/min at 7.25 and 0.0013 units/min at 7.20. Out of the alternative pH thresholds, 7.26 and 7.20 demonstrated the best alignment with our dataset. Multiple linear regression revealed that only pH value was significantly associated to the rate of pH change. Conclusions Our study confirms the validity and reliability of current guideline thresholds for fetal scalp pH in category II fetal heart rate.